The Effect of solvent, pH, extraction time and temperature on the extraction of phenolic compounds and antioxidant activity of Carpobrotus edulis - Laloo, N.; Terblanche, U.; Ssemakalu, C. C.; Pillay, M. (Journal of Phytology, 2023)
Two 23 factorial design studies were performed to determine the effect of solvent, pH, extraction time and temperature on the extraction of phenolics and radical scavenging activity contained in crude leaf extracts of Carpobrotus edulis. For the aqueous model, pH 9, 72 h and 40 °C provided the highest yield (31.03 ± 0.58%), while the highest yield for the methanolic extracts was obtained using the same temperature and pH, but with a longer extraction time of 168 h (64.21 ± 2.12%). Quantitative phytochemical analysis was performed to determine the amount of phenolics, tannins and flavonoids contained in the crude extracts. When water was used as an extraction solvent, the highest concentration of phenolics was obtained using pH 9 and extracting for 72 h at 40 °C (6.42 ± 0.03 milligrams Gallic Acid Equivalent per gram of extract). However, when methanol was used as a solvent, the highest concentration of phenolics was obtained when the same pH and time of extraction was used, but at a lower temperature (25 °C) – 7.44 ± 0.50 mg GAE/g of extract. Antioxidant activity was determined using the ABTS and DPPH assays. For both, methanol extracts produced lower IC50 values than the aqueous extracts. The best combination of extraction conditions for aqueous extracts is pH 9, and 72 h of extraction at 40 °C. This produced the lowest IC50 values for both assays (298.28 μg/mL for DPPH and 140.77 μg/mL for ABTS assay). When methanol is used as a solvent, the extraction conditions producing the lowest IC50 values were pH 9, 72 h and 25 °C for the DPPH assay (109.84 μg/mL), and pH 5, 168 h and 25 °C for the ABTS assay (26.79 μg/mL). These values are all higher than for the positive control, ascorbic acid. A positive correlation exists between phenolic content and radical scavenging activity – higher phenolic content resulted in higher radical scavenging activity. Pearson’s correlation coefficient was higher for the aqueous extracts than for the methanol extracts. Thus, extraction conditions must be modified to maximise extraction of phenolics, to obtain maximum radical scavenging activity.